Cardioprotective Potentials of Medicinal Plants: An Integrative Review of Herbal Interventions in Cardiovascular Disorders - Hasan, Rizwan Ul; Yadav, Sanjay Kumar; Ahmad, Rizwan; Alam, Sajjad; Ahmad, Rizwan; Kumar, Rinkesh (Journal of Neonatal Surgery, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality globally, largely attributed to sedentary lifestyles, unhealthy diets, psychological stress, and environmental factors. Although conventional pharmacological therapies exist, they often carry drawbacks such as adverse effects, high cost, and limited long-term efficacy. Traditional medicine systems—especially Siddha, an ancient Dravidian practice—offer promising botanical Rizwan Ul Hasan, Sanjay Kumar Yadav, Rizwan Ahmad, Sajjad Alam, Rizwan Ahmad, Rinkesh Kumar alternatives with cardioprotective potential. Siddha formulations, historically documented in palm-leaf manuscripts, incorporate numerous herbs with demonstrated cardiovascular benefits. This review comprehensively explores the cardioprotective efficacy of various medicinal plants, focusing on their phytoconstituents, pharmacological actions, and mechanisms of action. Plants such as Terminalia chebula, Piper longum, Zingiber officinale, Tinospora cordifolia, Asparagus racemosus, Andrographis paniculata, Nelumbo nucifera, Allium sativum, and Bauhinia variegata have shown significant effects in preclinical and clinical studies. Other botanicals like Azadirachta indica, Bacopa monnieri, Curcuma longa, Hygrophila auriculata, Nigella sativa, Ocimum basilicum, Terminalia arjuna, Withania somnifera, and Tribulus terrestris also exhibit therapeutic potential against myocardial infarction, hypertension, atherosclerosis, arrhythmias, and doxorubicin-induced cardiotoxicity. This review emphasizes the phytochemical richness and multi-targeted mechanisms of these herbs—ranging from antioxidant and anti-inflammatory actions to modulation of lipid profiles and vascular function. With nearly 80% of the global population relying on traditional medicine, integrating validated plant-based remedies into mainstream cardiovascular care could provide safer, more affordable, and holistic options for the prevention and management of CVDs.